Pharyngeal haematoma and partial airway obstruction caused by interaction between warfarin and topical miconazole gel. Issue 3 (2nd March 2021) - Reynolds, Heather
Abstract : A man in his 70s on warfarin attended the emergency department three times over a 24-hour period, complaining of a sore throat, neck swelling and difficulty swallowing. He was initially diagnosed with pharyngitis, given antibiotics and discharged home, which was reconfirmed on the second attendance after an episode of haemoptysis. On the third, he was diagnosed with a pharyngeal haematoma causing partial airway obstruction and admitted to critical care. His international normalised ratio (INR) was reported initially as unreadable by the laboratory, then eventually came back as >20. After a thorough medication history, he said that he had recently been prescribed topical miconazole oromucosal gel by his dentist for oral candidiasis, which had interacted with the warfarin to cause this life-threatening haematoma.